Alumina crucible and preparation method and use thereof

By using an alumina crucible, its inner surface is covered with lithium aluminum oxide layer, the problem of loss of lithium elements during sintering of LLZO solid electrolyte is solved, master powder sintering is achieved, production costs are reduced, and it is suitable for other volatile element ceramics. Sintering of materials.

CN115307434BActive Publication Date: 2025-02-25SHANGHAI TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210993235.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-18
Publication Date
2025-02-25
Estimated Expiration
2042-08-18

AI Technical Summary

Technical Problem

In the prior art, lithium lanthanum zirconium oxygen (LLZO) solid electrolyte has serious losses in the sintering process, resulting in increased production costs, and the crucibles using other materials are high, difficult production processes and high energy consumption.

Method used

Alumina crucible is used, and its crucible body consists of a pot body and a lid body. The pot body and lid body are made of aluminum oxide material, and the inner surface is covered with lithium aluminum oxide layer. It is prepared by 3D printing and heat treatment to form dense lithium aluminum oxide. layer.

Benefits of technology

The LLZO ceramic electrolyte material without master powder is realized, which reduces production costs, and the alumina crucible can be reused without causing loss of lithium. It is suitable for the sintering preparation of other volatile element ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115307434B_ABST
    Figure CN115307434B_ABST
Patent Text Reader

Abstract

The present invention provides an alumina crucible, comprising a crucible body, wherein the crucible body comprises a pot body and a cover body; the pot body and the cover body are made of alumina material, and at least the inner surfaces of the pot body and the cover body contain a lithium aluminum oxide layer; the alumina crucible of the present invention can realize mother powder-free sintering of LLZO ceramic electrolyte materials, and achieve an electrical conductivity similar to that of traditional methods; the present invention also provides a method for preparing an alumina crucible, which can prepare alumina crucibles of customized sizes, and the alumina crucible of the present invention can be used for the preparation of solid electrolyte ceramic sheets. The present invention also provides a method for preparing LLZO solid electrolyte ceramic sheets using an alumina crucible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to, in particular to, an alumina crucible and a preparation method and application thereof. Background Art

[0002] Lithium lanthanum zirconium oxide (LLZO) solid electrolyte has become a widely studied oxide solid electrolyte due to its advantages such as high lithium ion conductivity and wide electrochemical stability window. LLZO solid electrolyte is usually made by sintering for a long time at a temperature above 1100°C. Due to the serious loss of lithium in this process, researchers usually use "mother powder" of the same composition to cover LLZO to compensate for the loss of lithium in the electrolyte sheet. However, after the mother powder is used, a large amount of lithium is lost and it cannot be reused, which increases the production cost of LLZO solid electrolyte. Wen Zhaoyin's team studied the effects of different materials and crucibles of different sizes on the sintering effect of LLZO, and explained why the corundum crucible used in the traditional sintering method has Al content in the sintering process of LLZO solid electrolyte. 2 O 3 With Li 2 O reaction causes the lithium atmosphere in the sintering environment to be absorbed by the crucible, resulting in insufficient lithium, which causes the decrease of ionic conductivity and density of solid electrolyte. In addition, excessive crucible volume will also dilute the concentration of lithium atmosphere in the environment. Finally, it is proposed to use MgO or platinum which will not react with Li 2 Crucibles made of materials that react with O can achieve good mother powder-free sintering effects.

[0003] However, platinum crucibles are expensive, and MgO crucibles are more expensive, more difficult to produce, and consume more energy than traditional corundum crucibles. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide an alumina crucible and a preparation method and use thereof, so as to solve the problem of lithium loss when sintering LLZO solid electrolyte in a corundum crucible in the prior art, and the problem of high production cost caused by using other crucibles.

[0005] To achieve the above-mentioned purpose and other related purposes, the present invention provides an alumina crucible, including a crucible body, the crucible body including a pot body and a cover body; the pot body and the cover body are made of alumina material, and at least the inner surfaces of the pot body and the cover body are covered with a lithium aluminum oxide layer.

[0006] Preferably, the crucible body is cylindrical; the pot body is composed of a crucible bottom plate and a crucible side wall, and the crucible side wall is arranged around the periphery of the crucible bottom plate to form a pot body cavity; optionally, a step is formed on the inner side surface of the crucible side wall for placing the cover body; optionally, in the closed state, the top of the cover body is flush with the top of the crucible side wall.

[0007] Preferably, the lithium aluminum oxide layer comprises a surface layer of LiAlO 2 Layer and inner layer LiAl 5 O 8 layer.

[0008] Preferably, the average particle size of the lithium aluminum oxide layer is 3 to 10 μm.

[0009] Preferably, the pot body and the lid body are obtained by 3D printing.

[0010] The present invention also provides a method for preparing the above-mentioned alumina crucible, comprising the following steps:

[0011] S1. Prepare a crucible using alumina as raw material;

[0012] S2. Heat-treating the crucible obtained in step S1 to obtain the alumina crucible as described above.

[0013] Preferably, in step S1, the surface morphology of the crucible is loose and porous, and the Al 2 O 3 The particle size is less than 5 μm.

[0014] Preferably, in step S1, the crucible is obtained by 3D printing and undergoing a degumming and densification process.

[0015] Preferably, in step S2, the heat treatment comprises any one of the following methods:

[0016] a. Suspend the crucible of step S1 on Li 2 O powder is sintered in a high temperature sintering furnace;

[0017] b. Place the LLZO powder inside the crucible of step S1 and sinter it in a high-temperature sintering furnace.

[0018] The present invention also provides an application of the above-mentioned alumina crucible in the preparation of solid electrolyte ceramic sheets.

[0019] The present invention also provides a method for preparing a LLZO solid electrolyte ceramic sheet, comprising the following steps:

[0020] 1) Preparing LLZO green body from LLZO powder;

[0021] 2) The LLZO green body obtained in step 1) is placed in the above-mentioned alumina crucible, placed in a high-temperature sintering furnace for sintering, taken out after cooling in the furnace, and polished to obtain a LLZO solid electrolyte ceramic sheet.

[0022] Preferably, the preparation of the LLZO green body in step 1) is as follows: 2 O 3The powder is mixed with LLZO powder, sieved, added into a tableting mold and tableted to obtain LLZO green body;

[0023] Preferably, the temperature of the high temperature sintering furnace in step 2) is 1200-1300°C, and the heating rate is 2-10°C min -1 The sintering holding time is 20min~2h.

[0024] As described above, the alumina crucible of the present invention and its preparation method and use have the following beneficial effects:

[0025] 1) The alumina crucible of the present invention can realize the sintering of LLZO ceramic electrolyte material without mother powder, and the solid electrolyte prepared by sintering without mother powder using the alumina crucible can achieve performance similar to that of the solid electrolyte prepared by the traditional mother powder covering sintering method.

[0026] 2) The alumina crucible of the present invention is reusable and will not cause lithium loss during the sintering process of LLZO solid electrolyte, which not only effectively reduces the production cost of LLZO solid electrolyte ceramic materials, but can also be applied to the sintering preparation of other ceramic materials with volatile elements.

[0027] 3) The present invention also prepares alumina crucibles of customized sizes through 3D printing technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of an alumina crucible according to the present invention is shown I: a. Schematic diagram; b. Digital photo.

[0029] Figure 2 Schematic diagram II of the alumina crucible of the present invention is shown, wherein: 1, pot body; 2, cover body; 11, crucible bottom plate; 12, crucible side wall; 111, protrusion; 121, first inner side surface; 122, second inner side surface.

[0030] Figure 3 Shown are the micromorphology of the alumina crucible before heat treatment: a. surface micromorphology; b. cross-sectional micromorphology.

[0031] Figure 4 The XRD spectrum of the alumina crucible after heat treatment is shown: a. The crucible is suspended on Li 2 O powder, keep at 1250℃ for 40min; b. The crucible is suspended on Li 2 O powder and keep warm at 1250℃ for 2h.

[0032] Figure 5 Shown is the microstructure of the alumina crucible after heat treatment: a. 2 The microscopic morphology of the crucible surface after O powder was kept at 1250℃ for 40min; b.2 O powder 1250 ℃ for 2h crucible surface microstructure; c. Li 2 Microscopic morphology of the crucible cross section of O powder kept at 1250℃ for 40min; d. 2 Microstructure of the cross section of a crucible in which O powder was kept at 1250℃ for 2h.

[0033] Figure 6 Display as Li 2 XRD spectra of the alumina crucible with O powder kept at 1250℃ for 2h after the surface was polished away by 10, 20, and 70μm respectively.

[0034] Figure 7 Shown are the room temperature ionic conductivity and relative density of LLZO sintered in the alumina crucible of the present invention without mother powder: a. Crucible after LLZO heat treatment; b. 2 O heat treated crucible. DETAILED DESCRIPTION

[0035] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0036] See also Figures 1 to 7 It should be noted that the illustrations provided in this embodiment are only used to illustrate the basic concept of the present invention in a schematic manner, and the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0037] On one hand, the present invention provides an alumina crucible, including a crucible body, the crucible body including a pot body 1 and a cover body 2; the pot body 1 and the cover body 2 are both made of alumina, and at least the inner surfaces of the pot body 1 and the cover body 2 are covered with a lithium aluminum oxide layer.

[0038] The alumina crucible of the present invention is made of alumina, and at least the inner surfaces of the pot body 1 and the cover body 2 are covered with a lithium aluminum oxide layer. It is not only suitable for high-temperature mother powder-free sintering preparation of ceramic materials containing volatile elements in the alumina crucible, but also can ensure the stability of the crucible for repeated use.

[0039] In the alumina crucible of the present invention, the crucible body is cylindrical; the pot body 1 is composed of a crucible bottom plate 11 and a crucible side wall 12, and the crucible side wall 12 is arranged around the periphery of the crucible bottom plate 11 to form a pot body cavity; optionally, a step is formed on the inner side surface of the crucible side wall 12 for placing the cover body; optionally, in the closed state, the top of the cover body 2 is flush with the top of the crucible side wall 12.

[0040] Among them, the crucible side wall 12 is formed with a step for placing the cover body by two inner side surfaces of different diameters, including a first inner side surface 121 and a second inner side surface 122. The first inner side surface 121 is integrally connected to the crucible bottom plate 11, and the diameter of the first inner side surface 121 is smaller than that of the second inner side surface 122; the diameter of the cover body 2 is larger than the diameter of the first inner side surface 121, and less than or equal to the diameter of the second inner side surface 122.

[0041] A plurality of cylindrical protrusions 111 are evenly arranged on the inner side of the crucible bottom plate 11. Figure 1 As shown in b, four small cylindrical protrusions 111 are provided, which can make the ceramic sheet be heated more evenly when it is subsequently used to sinter the electrolyte ceramic sheet, thereby reducing the possibility of the ceramic sheet being bonded to the bottom of the crucible.

[0042] In the alumina crucible of the present invention, the lithium aluminum oxide layer includes a surface layer LiAlO 2 Layer and inner layer LiAl 5 O 8 The average particle size of the lithium aluminum oxide layer is 3 to 10 μm. The pot body and the lid are obtained by 3D printing.

[0043] A second aspect of the present invention provides a method for preparing an alumina crucible, comprising the following steps:

[0044] S1. Prepare a crucible using alumina as raw material;

[0045] S2. Heat-treating the crucible obtained in step S1 to obtain the alumina crucible as described above.

[0046] In step S1, the crucible surface morphology is loose and porous, and the Al 2 O 3 The particle size is less than 5 μm. In a preferred embodiment of the present invention, the Al 2 O 3 The particle size is less than 1 μm. The loose porous structure of the crucible is convenient for heat treatment to obtain an alumina crucible with better performance.

[0047] In step S1, the crucible is 3D printed and obtained through degumming and densification processes. 2 O 3The ceramic slurry is printed into a crucible through a 3D printer. The specific process of the 3D printing process is as follows: the pre-designed crucible three-dimensional model data is imported into the 3D printer. The model design needs to adapt to the size and number of electrolyte sheets to ensure a relatively compact sintering space to maintain the concentration of lithium atmosphere during the sintering process. 2 O 3 The ceramic slurry is placed on the printing platform, and the 3D printer (laser wavelength is 355nm) is operated to solidify the ceramic slurry layer by layer to print out the crucible. By adjusting the light intensity, the solidification depth of the slurry in a single laser scan is about 400μm. In order to ensure the bonding strength between layers and printing efficiency, the printing layer thickness is set to 100μm (about 1 / 3-1 / 4 of the solidification depth). After the model is printed, take out the crucible, wipe it clean with paper, and rinse off the residual slurry on the surface with ethanol. Among them, the 3D printer models used are: Inteli Laser Technology Company CeraBuilder 100; Al 2 O 3 The ceramic slurry was purchased from Inteli Laser Technology Co., Ltd.

[0048] Degumming is to place the crucible obtained in step S1 in a box furnace, and keep it at 250-350°C and 510-610°C respectively, with a holding time of ≥1h and a heating rate of ≤5°Cmin -1 In a preferred embodiment of the present invention, the crucible is placed in a box furnace and kept at 300°C and 560°C for 2h respectively, with a heating rate of 2°C min -1 .

[0049] Densification is to cool the debonded crucible and transfer it to a high-temperature sintering furnace, heating it to 1200-1400°C, with a heating rate of ≤5°C min -1 , keep warm for 1 to 4 hours, cool down with the furnace and take out to obtain a densified crucible. In a preferred embodiment of the present invention, after degumming, the crucible is cooled and transferred to a high-temperature sintering furnace, heated to 1300°C, and the heating rate is 2°C min -1 , keep warm for 2h.

[0050] In the method for preparing an alumina crucible of the present invention, in step S2, the heat treatment is any one of the following methods:

[0051] a. Suspend the crucible of step S1 on Li 2 O powder is sintered in a high temperature sintering furnace;

[0052] b. Place the LLZO powder inside the crucible of step S1 and sinter it in a high-temperature sintering furnace.

[0053] The crucible prepared in step S1 is heat treated to form a dense protective layer on the surface of the crucible, and the protective layer is a lithium aluminum oxide layer.

[0054] In method a, the sintering conditions are 1100-1300°C for 40 min-5 h, and a heating rate of 1-10°C min -1 In a preferred embodiment of the present invention, the sintering conditions are 1250°C for 2 hours and the heating rate is 5°C min -1 The specific process of method a is as follows: hang the crucible in the air over Li 2 About 1-2 cm above the O powder, use a high-temperature sintering furnace to keep the temperature at 1250℃ for 2 hours, with a heating rate of 5℃min -1 After cooling down in the furnace, take it out and get an alumina crucible. When suspended in the air, the crucible mouth faces downward and hangs in an upside-down state on the Li 2 O above the powder.

[0055] In method b, the sintering conditions are 1100-1300°C for 40 min-5 h, with a heating rate of 1-10°C min -1 In a preferred embodiment of the present invention, the sintering conditions are 1250°C for 2 hours and the heating rate is 5°C min -1 The specific process of method b is as follows: LLZO powder is filled into the crucible, and a high-temperature sintering furnace is used to keep the temperature at 1250℃ for 2h, with a heating rate of 5℃min -1 , take it out after cooling down in the furnace to obtain an alumina crucible.

[0056] In method b, the LLZO powder includes LLZO powder containing doping elements, such as LLZTO powder (Ta-doped LLZO).

[0057] The preparation method of the alumina crucible of the present invention comprises the following steps: heat-treating the prepared crucible with a loose and porous surface morphology to form a dense lithium aluminum oxide layer on the surface of the crucible, thereby ensuring the stability of the crucible for repeated use.

[0058] A third aspect of the present invention provides an application of an alumina crucible in the preparation of a solid electrolyte ceramic sheet.

[0059] A fourth aspect of the present invention provides a method for preparing a LLZO solid electrolyte ceramic sheet, comprising the following steps:

[0060] 1) Preparing LLZO green body from LLZO powder;

[0061] 2) The LLZO green body obtained in step 1) is placed in the alumina crucible as described above, placed in a high-temperature sintering furnace for sintering, taken out after cooling in the furnace, and polished to obtain a LLZO solid electrolyte ceramic sheet.

[0062] In the method for preparing the LLZO solid electrolyte ceramic sheet of the present invention, the preparation of the LLZO green body in step 1) is as follows: 2 O 3The powder is mixed with LLZO powder, sieved, and added to a tableting mold to obtain a LLZO green body. The specific process is: add 2wt% Al to the LLZO powder. 2 O 3 The powder is used as a sintering aid. After mixing, it is sieved with a 400-mesh screen. A certain amount of the mixed powder is weighed and poured into a tablet pressing mold. A certain pressure is applied and maintained at the pressure for two minutes. The LLZO green body is taken out.

[0063] Preparation of LLZO powder: LiOH·H 2 O.La 2 O 3 、ZrO 2 Mix according to the stoichiometric ratio of the elements (add 20% excess LiOH·H 2 O is used to compensate for the volatilization of lithium during high-temperature calcination) in isopropanol, ball-milled at 600 rpm for 6 h, and calcined at 950 ° C for 6 h to obtain LLZO powder. If Ta-doped LLZO powder is prepared, a stoichiometric ratio of Ta is added to the raw material. 2 O 5 Similarly, LLZO powder doped with other elements can also be prepared.

[0064] The temperature of the high temperature sintering furnace in step 2) is 1200-1300°C, and the heating rate is 2-10°C min -1 , the sintering holding time is 20min to 2h. In a preferred embodiment of the present invention, the high temperature sintering furnace temperature is 1250°C, and the heating rate is 5°C min -1 , the insulation time is 40min.

[0065] The sintering in step 2) is sintering without mother powder.

[0066] The specific process is as follows: the LLZO green body prepared in step 1) is placed in an alumina crucible without covering the mother powder, and a high-temperature sintering furnace is used to keep the temperature at 1250°C for 40 minutes, with a heating rate of 5°C min -1 After cooling in the furnace, take it out and polish it with 800, 1500 and 2000 grit sandpaper respectively until a smooth LLZO surface is obtained.

[0067] The alumina crucible of the present invention is also suitable for ceramic materials such as perovskite electrolyte lithium lanthanum titanate (LLTO), NASICON solid electrolyte lithium aluminum titanium phosphate (LATP), sodium zirconium silicon phosphate (NZSP), etc., in which elements such as lithium or sodium are volatilized during the sintering process, so as to achieve mother powder-free sintering and reduce production costs.

[0068] Example 1

[0069] 3D Printing of Crucible:

[0070] Prepare Al 2 O 3 Ceramic slurry, import the designed crucible 3D model into the 3D printer (take the prepared crucible suitable for accommodating a piece of LLZO green body pressed by a 0.5-inch mold as an example): the crucible body is cylindrical, the crucible body is 3.5mm high, the crucible bottom plate 11 is 1mm thick, the outer diameter of the crucible side wall 12 is 24mm, the diameter of the first side inner surface 121 is 16mm, the cylindrical cavity formed by the first side surface 121 and the crucible bottom plate 11 is 1.5mm high, the diameter of the second inner surface 122 is 20mm, the diameter of the cover 2 is 19mm, and the thickness of the cover 2 is 1mm. 2 O 3 The ceramic slurry is placed on the printing platform, and the 3D printer (laser wavelength is 355nm) is operated to solidify the ceramic slurry layer by layer. The printing layer thickness is set to 100μm, and the crucible is printed. Wipe with paper and use an air gun to clean the residual printing slurry on the surface of the crucible. Then put the crucible into a small box furnace for degumming, so that the solidified polymer in it decomposes and detaches in the air. The degumming process is to keep the temperature at 300℃ and 560℃ for 2h respectively, and the heating rate is 2℃min -1 After cooling in the furnace, take it out and transfer it to a high-temperature sintering furnace, and heat it to 1300℃ to densify the crucible. The heating rate is 2℃min -1 , keep warm for 2h, cool down in the furnace and take out. Figure 1 b shows the crucible.

[0071] The crucible was observed by electron microscope (JSM-7800F, JEOL Ltd.) Figure 2 Surface and cross-sectional morphologies shown.

[0072] Depend on Figure 3 It can be seen that Al 2 O 3 The average particle size is less than 1 μm, and the loose structure is conducive to the subsequent 2 O forms a dense lithium aluminum oxide layer during heat treatment.

[0073] Example 2

[0074] The same method and data as in Example 1 were used to 3D print the crucible, and the crucible was heat treated:

[0075] The printed crucible was suspended in the air over about 0.2 g of Li 2 1-2 cm above the O powder, use a high temperature sintering furnace to keep the temperature at 1250℃ for 40 min, with a heating rate of 5℃min -1 , and then taken out after cooling down in the furnace to obtain an alumina crucible.

[0076] The alumina crucible was subjected to XRD test (Bruker D2 Powder X-ray Diffractometer, Germany), and the following results were obtained: Figure 4 Phase analysis results of a.

[0077] The alumina crucible was observed by electron microscope (JSM-7800F, JEOL Ltd.), and the following Figure 5 Surface and cross-sectional morphologies shown in a and c.

[0078] Example 3

[0079] The same method and data as in Example 1 were used to 3D print the crucible, and the crucible was heat treated:

[0080] The printed crucible was suspended in the air over about 0.2 g of Li 2 1-2 cm above the O powder, use a high temperature sintering furnace to keep the temperature at 1250℃ for 2h, with a heating rate of 5℃min -1 , and then taken out after cooling down in the furnace to obtain an alumina crucible.

[0081] The alumina crucible was subjected to XRD test (Bruker D2 Powder X-ray Diffractometer, Germany), and the following results were obtained: Figure 4 b Phase analysis results.

[0082] The alumina crucible was observed by electron microscope (JSM-7800F, JEOL Ltd.), and the following Figure 5 b and d show the surface and cross-sectional morphologies.

[0083] By embodiment 2~3 and attached Figure 4 It can be seen that with the increase of heat treatment time, LiAlO 2 Signal enhancement, LiAl 5 O 8 With Al 2 O 3 The signal weakened, and the Al 2 O 3 The signal is very small, which means that the aluminum oxide within tens of microns below the crucible surface has been almost completely converted into lithium aluminum oxide.

[0084] By embodiment 2~3 and attached Figure 5 It can be seen that with the increase of treatment time, the morphology of the surface of the alumina crucible is similar to 5a and 5b, which is a dense LiAlO with a particle size distribution of about 3-10μm. 2 However, from the cross-sectional images (5c and 5d), it can be seen that the thickness of the dense layer increases from about 5 μm after 40 min of treatment to about 15 μm after 2 h of treatment, which is consistent with Figure 4 The XRD results are consistent with those of

[0085] Example 4

[0086] The crucible was 3D printed using the same method as in Example 1, and heat treated using the same method as in Example 3 to obtain an alumina crucible. The surface of the alumina crucible was polished off by 10, 20, and 70 μm, respectively, and then XRD tests were performed. The results are as follows Figure 6 shown.

[0087] By Example 4 and Figure 6 It can be seen that: comparing the initial surface with the result after grinding 10μm, it is found that the representative LiAlO 2 The signals (22.3°, 33.4°, 34.7°) are greatly weakened, and because the surface shielding is worn away, LiAl 5 O 8 The signals (32°, 37.7°, 45.9°) are slightly enhanced. When a total of 20 μm is further polished away, LiAlO 2 The signal of LiAl completely disappeared. 5 O 8 The signal is still the strongest. 2 O 3 Finally, when a total of 70 μm was removed, LiAl 5 O 8 The signal completely disappeared, leaving only Al 2 O 3 This data further proves that Figure 5 The upper dense layer in the cross-sectional view (5c and 5d) is LiAlO 2 .

[0088] Example 5

[0089] The crucible was 3D printed using the same method and data as in Example 1, and heat treated: LLZO powder was filled into the crucible, and a high-temperature sintering furnace was used to keep the temperature at 1250°C for 2h, with a heating rate of 5°C min -1 , and then taken out after cooling down in the furnace to obtain an alumina crucible.

[0090] Preparation of Ta-doped LLZO solid electrolyte green body: chemical formula is Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO) was synthesized by traditional solid phase sintering. 2 O.La 2 O 3 、ZrO 2 、 2 O5 Mix according to the stoichiometric ratio of the elements (add 20% excess LiOH·H 2 O is used to compensate for the volatilization of lithium during high-temperature calcination) in isopropanol, ball-milled at 600 rpm for 6 h, and calcined at 950 ° C for 6 h to obtain LLZTO powder. Subsequently, 2 wt% Al was added to the LLZO powder. 2 O 3 The powder is used as a sintering aid. After mixing, it is sieved with a 400-mesh sieve. About 0.4 g of powder is weighed and poured into a tablet pressing mold with a diameter of 0.5 inches. The pressure is maintained for 2 minutes at a pressure of 4 MPa displayed on the press (the actual pressure on the tablet is about 300 MPa). The LLZTO solid electrolyte green body with a diameter of 1.27 cm is obtained.

[0091] The LLZTO green body was placed in the alumina crucible prepared in this embodiment without covering the mother powder, and a high-temperature sintering furnace was used to keep the temperature at 1250°C for 40 minutes, with a heating rate of 5°C min -1 After cooling in the furnace, the ceramic sheet was taken out and polished with 800, 1500 and 2000 grit sandpapers respectively until a smooth surface of the LLZTO solid electrolyte ceramic sheet was obtained.

[0092] The LLZTO solid electrolyte ceramic sheet was gold-sprayed on both sides, and its ionic conductivity and density were tested. Figure 7 As shown in a.

[0093] Example 6

[0094] The crucible was 3D printed using the same method and data as in Example 1, and heat treated using the same method as in Example 3 to obtain an alumina crucible.

[0095] The Ta-doped LLZO green body was prepared in the same manner as in Example 5 to obtain a LLZTO solid electrolyte green body.

[0096] The prepared LLZTO solid electrolyte green body was placed in the alumina crucible prepared in this example without covering the mother powder, and a high-temperature sintering furnace was used to keep the temperature at 1250°C for 40 minutes, with a heating rate of 5°C min -1 After cooling in the furnace, the ceramic sheet was taken out and polished with 800, 1500 and 2000 grit sandpapers respectively until a smooth surface of the LLZTO solid electrolyte ceramic sheet was obtained.

[0097] The LLZTO solid electrolyte ceramic sheet was gold-sprayed on both sides, and its ionic conductivity and density were tested. Figure 7 As shown in b.

[0098] From Examples 5 to 6 and the attached Figure 7It can be seen that the alumina crucibles prepared by different heat treatment methods in Example 5 and Example 6 have similar performances when used for sintering LLZTO solid electrolyte ceramic sheets, and the room temperature ionic conductivity reaches 2.8×10 -4 S cm -1 (average value), and the relative density is 91.5% (average value). This indicates that the basic performance parameters of the LLZTO solid electrolyte prepared by the method of the present invention as a solid electrolyte for all-solid-state lithium batteries are relatively ideal.

[0099] From the above data, it can be seen that the method of heat treating the crucible by filling the LLZO powder into the crucible in Example 5 is different from the method of heat treating the crucible by suspending the crucible in the Li 2 The performance of the alumina crucible obtained by the method of heat treatment on the top of O powder is similar. At the same time, the performance of the LLZTO solid electrolyte ceramic sheet sintered by the alumina crucible of the present invention without mother powder is similar to that of the LLZTO solid electrolyte ceramic sheet sintered by the traditional method with mother powder, and compared with the existing platinum crucible sintering technology without mother powder, the cost of the alumina crucible of the present invention is lower.

[0100] Example 7

[0101] The crucible was 3D printed using the same method and data as in Example 1 and heat treated (using commercial sodium zirconium silicon phosphorus oxide NZSP (Na 3 Zr 2 Si 2 PO 12 ) powder was subjected to heat treatment), specifically: the crucible was suspended 1-2 cm above about 0.2 g of NZSP powder, and a high-temperature sintering furnace was used to keep the temperature at 1250°C for 2 h, with a heating rate of 5°C min -1 , and then taken out after cooling in the furnace to obtain an alumina crucible treated with NZSP.

[0102] The NZSP green body is obtained by pressing NZSP powder. About 0.4 g of NZSP powder is weighed and poured into a tablet pressing mold with a diameter of 0.5 inches. The pressure is maintained for 2 minutes at a pressure of 4 MPa displayed on the press (the actual pressure acting on the tablet is about 300 MPa). The NZSP solid electrolyte green body with a diameter of 1.27 cm is obtained.

[0103] The NZSP solid electrolyte green body was placed in the NZSP treated alumina crucible prepared in this example without covering the mother powder, and a high temperature sintering furnace was used to keep the temperature at 1200°C for 6 hours, with a heating rate of 5°C min -1 After cooling in the furnace, the ceramic sheet was taken out and polished with 800, 1500 and 2000 grit sandpapers respectively until a smooth surface of the NZSP solid electrolyte ceramic sheet was obtained.

[0104] The NZSP solid electrolyte ceramic sheet was double-sided sprayed with gold, and the density and ion conductivity were tested. The ion conductivity and density of the NZSP solid electrolyte ceramic sheet of Example 7 were similar to the electrolyte performance obtained by sintering without mother powder using the traditional sintering method.

[0105] In summary, the alumina crucible of the present invention makes cheap Al 2 O 3 The crucible is applied to the method of sintering solid electrolyte without mother powder, and can obtain LLZO solid electrolyte with similar performance to the traditional mother powder covering sintering method, reducing the production cost of LLZO solid electrolyte. At the same time, the preparation method of the alumina crucible of the present invention is also applicable to the sintering of other ceramic materials, such as perovskite electrolyte lanthanum lithium titanate (LLTO), NASICON solid electrolyte lithium aluminum titanium phosphate (LATP), sodium zirconium silicon phosphorus oxygen (NZSP), etc., which have elements such as lithium or sodium volatilized during the sintering process, so as to achieve mother powder-free sintering and reduce production costs. Therefore, the present invention effectively overcomes various shortcomings in the prior art and has high industrial utilization value.

[0106] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. An alumina crucible, comprising a crucible body, characterized in that: The crucible body comprises a pot body and a cover body; the pot body and the cover body are made of alumina, and at least the inner surfaces of the pot body and the cover body are covered with a lithium aluminum oxide layer; the lithium aluminum oxide layer comprises a surface LiAlO2 layer and an inner LiAl5O8 layer; the crucible body is cylindrical; the pot body is composed of a crucible bottom plate and a crucible side wall, and the crucible side wall is arranged around the periphery of the crucible bottom plate to form a pot body cavity, and a step is formed on the inner side surface of the crucible side wall to place the cover body, and in the closed state, the top of the cover body is flush with the top of the crucible side wall; a plurality of cylindrical protrusions are evenly arranged on the inner side surface of the crucible bottom plate, and the pot body and the cover body are obtained by 3D printing; The preparation method of the alumina crucible comprises the following steps: S1. Prepare a crucible using alumina as raw material; S2, heat treating the crucible obtained in step S1 to obtain an alumina crucible; In step S1, the surface morphology of the crucible is loose and porous, and the average particle size of Al2O3 particles is less than 5 μm; In step S1, the crucible is 3D printed and obtained through degumming and densification processes; the degumming is to place the crucible obtained in step S1 in a box furnace, and keep it at 250-350°C and 510-610°C respectively, with a holding time of ≥1 h and a heating rate of ≤5°C min -1 , so that the solidified polymer in the crucible is decomposed and separated to obtain a debonded crucible; the densification is to place the debonded crucible in a high-temperature sintering furnace, heated to 1200~1400℃, and the heating rate is ≤5℃ min -1 , keep warm for 1-4 h, cool down with the furnace and take out to obtain the densified crucible; In step S2, the heat treatment includes the following method: placing LLZO powder inside the crucible of step S1 and sintering it in a high-temperature sintering furnace; heat treating the prepared crucible with loose and porous surface morphology to form a dense lithium aluminum oxide layer on the surface of the crucible to ensure the stability of the crucible for repeated use; Preparation of LLZO powder: The raw materials LiOH·H2O, La2O3, and ZrO2 were mixed in isopropanol according to the stoichiometric ratio of the elements, and 20% excess LiOH·H2O was added to compensate for the volatilization of lithium during the high-temperature calcination process. The mixture was ball-milled at 600 rpm for 6 h and calcined at 950 °C for 6 h to obtain LLZO powder. The alumina crucible can realize mother powder-free sintering of LLZO ceramic electrolyte materials.

2. The alumina crucible according to claim 1, characterized in that: The average particle size of the lithium aluminum oxide layer is 3-10 μm.

3. The alumina crucible according to claim 1, characterized in that: Includes any of the following characteristics: b1. The sintering conditions are 1100~1300 ℃ for 40 min~5 h, and the heating rate is 1~10 ℃ min -1 ; b2. The LLZO powder includes LLZO powder containing a doping element.

4. Use of the alumina crucible according to any one of claims 1 to 3 in the preparation of solid electrolyte ceramic sheets.

5. A method for preparing a LLZO solid electrolyte ceramic sheet, characterized in that: The following steps are involved: 1) Preparation of LLZO green body from LLZO powder; 2) The LLZO green body obtained in step 1) is placed in the alumina crucible according to any one of claims 1 to 3, placed in a high-temperature sintering furnace for sintering, taken out after cooling in the furnace, and polished to obtain a LLZO solid electrolyte ceramic sheet.

6. The method for preparing the LLZO solid electrolyte ceramic sheet according to claim 5, characterized in that: In step 1), the LLZO green body is prepared by mixing Al2O3 powder and LLZO powder, sieving, adding the mixture into a tableting mold, and tableting to obtain the LLZO green body; And / or, the high temperature sintering furnace temperature in step 2) is 1200-1300°C, and the heating rate is 2-10°C min -1 The sintering holding time is 20 min~2h.

Citation Information

Patent Citations

  • Microwave assisted technical method for preparing lithium-lanthanum-zirconium-oxygen solid electrolyte

    CN105811000A

  • Device and method for improving purity of aluminum nitride crystal growth raw material

    CN112210833A